A cross-sectional assessment of knowledge, awareness of risk factors, and perceptions of thyroid disease (TD) among adults living in Saudi Arabia – A community based study - Alhazmi, Riyadh A.; Alobaid, Abdullah M.; Althunayyan, Saqer Mohammed; Syed, Wajid; Al-Rawi, Mahmood Basil A. (Frontiers in Public Health, 2022)
Background The incidence of thyroid diseases has tripled in the last three decades, and the prevalence is rising rapidly irrespective of gender and genetics. This study aimed to assess the Knowledge, awareness of risk factors, and perceptions of thyroid disease among the Saudi Community in Saudi Arabia. Methods A cross-sectional, online web-based, survey type study was conducted between November 2021 to January 2022 among residents living in Saudi Arabia. Individuals aged ≥ 18 years who expressed a willingness to complete the survey were included. Descriptive and bivariate analyses were carried out to determine the factors associated with knowledge of thyroid using SPSS version 26.0 software (SPSS Inc., Chicago, IL, U.S.). Results Among the participants, the majority of them were females than males (77.5 vs. 22.5%). A total of 78.2% (n = 566) of them were aware of the thyroid. Nearly 44% (n = 312) of respondents are aware that a lump in the neck or swelling is a sign of thyroid disease, followed by pain in the neck 24.6% (n = 178), and difficulty in swallowing 23.8% (n = 172). The mean knowledge score of the thyroid was 4.1 (SD = 3.09), while the score of the mean perception was 33.02 (SD = 6.41). The mean knowledge scores were significantly associated with having previous knowledge of thyroid disease (t = 5.08; p = 0.0001). The gender of the participant and the presence of chronic diseases were found to have no impact on the knowledge score of the thyroid disease (t = −1.18; p = 0.235; t = 1.005; p = 0.315). Additionally, the perceptions score was not significantly associated with the demographics of the participants (p = 0.05). Conclusion In this study, Saudi adults reported varying levels of knowledge and perceptions of thyroid disease. Having previous knowledge of the thyroid was significantly associated with the knowledge score. It is necessary to educate people about this rising disease.